Music, ballet, mindfulness, and psychological inflexibility - Serrano, Telmo (2017)
Both music and dance training can be conceptualised as mindfulness-like practices due to their focus on the present moment. Mindfulness and music are associated with mental health. However, evidence from dance practice, especially among ballet students, shows an association with mental health problems. Psychological inflexibility involves cognitive fusion, which is an excessive involvement with internal events, leading to experiential avoidance. Since studies analysing these concepts are scarce in music and dance practice, we intended to examine their effects in young music and ballet students. This study involved 113 participants (9 to 16 years old), 64.4% girls, 34.5% with musical training, 29.2% with ballet training, and 36.3% with no training. All participants completed the Child and Adolescent Mindfulness Measure (CAMM) and the Avoidance and Fusion Questionnaire for Youth (AFQ-Y). AFQ-Y scores correlated with months of ballet training. Ballet students had greater psychological inflexibility than music students and students without any training. CAMM scores did not correlate with months of any practice, and did not distinguish between groups of practitioners. These data confirm prior findings that practice of ballet can have a potential impact on mental health by showing that young ballet students exhibit greater psychological inflexibility.